2021
DOI: 10.29333/ejmste/11102
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teacher Experiences of the 5E Instructional Model: A Systematic Review of Qualitative Studies

Abstract: This systematic review of qualitative studies was conducted to identify the factors that influence how pre-service science/math teachers implement the 5E instructional model and the challenges and barriers they face in doing so. Sixteen studies were identified in various electronic databases, and a meta-ethnography method was used to review the qualitative studies. The findings illustrate that the experiences of the pre-service teacher varied. Time, resources, method courses, training, field experience, belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The 5E educational model was one of the most effective teaching methods for pre-service science teachers learning. In another study by Turan (2021) using the meta-ethnographic method, which examines the systematic examination of qualitative studies addressing the difficulties faced by pre-service teachers while applying the 5E educational model, time, resources, beliefs, content, and class size were determined as the obstacles in the implementation of the 5E educational model by the pre-service teachers. Anil and Batdi (2015) reviewed the quantitative studies carried out in Turkey and published in the national and international literature over the period 2008 to 2014 about the effect of the 5E educational model on students' academic achievement, retention, and attitude scores.…”
Section: Discussionmentioning
confidence: 99%
“…The 5E educational model was one of the most effective teaching methods for pre-service science teachers learning. In another study by Turan (2021) using the meta-ethnographic method, which examines the systematic examination of qualitative studies addressing the difficulties faced by pre-service teachers while applying the 5E educational model, time, resources, beliefs, content, and class size were determined as the obstacles in the implementation of the 5E educational model by the pre-service teachers. Anil and Batdi (2015) reviewed the quantitative studies carried out in Turkey and published in the national and international literature over the period 2008 to 2014 about the effect of the 5E educational model on students' academic achievement, retention, and attitude scores.…”
Section: Discussionmentioning
confidence: 99%
“…This tripartition can be expanded into more parts to allow learners to delve deeper into the given subject matter. The 5Emodel was developed based on constructivist learning theory and cognition psychology as well as proven methods in science education (Duran and Duran, 2004) to create lessons in a student instead of teacher centered way (Turan, 2021). The model can be used within single or few hours as well as for longer units.…”
Section: The 5e-modelmentioning
confidence: 99%
“…Nevertheless, studies also showed that it is hard for teachers to find suitable activities and materials for different phases of the 5E-Model (Namdar and Kucuk, 2018). Furthermore, several studies have shown different barriers, like classroom management and time issues, that hinder teachers from implementing the 5E into their own lesson planning (Turan, 2021).…”
Section: The 5e-modelmentioning
confidence: 99%
“…Duran and Duran (2004) examined the 5E learning model and its use in several career skills development science curricula. According to the results of the research on the effectiveness of the 5E model, Turan (2021) suggests several areas of research on the 5E learning model in the future. Another area of research in science and humanities teachers' different experiences in their view of the 5E learning model (Turan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of the research on the effectiveness of the 5E model, Turan (2021) suggests several areas of research on the 5E learning model in the future. Another area of research in science and humanities teachers' different experiences in their view of the 5E learning model (Turan, 2021). In their study, Anwari et al (2015) point out that knowledge, intelligence, experience, and practice are important components of improving metacognitive skills.…”
Section: Introductionmentioning
confidence: 99%